Livros literários infantis digitais interativos em formato de aplicativos: análise de práticas multiletradas na formação de leitores - Machado, Paulo Henrique (2019)
This study aims to analyze the multiliteracies practices mobilized by picturebook apps that contribute to the formation of the literary reader in childhood. In order to do so, itwas delimited as a corpus of research three picturebook apps finalists of the BolognaRagazzi Digital Award (Bologna Children’s Book Fair, Italy) in the year 2016 – “Wuwu & Co.” (HELLE; SLOCINSKA, 2015), “Chomp” (NIEMANN, 2016) and “Goldilocks and Little Bear” (NOSY CROW, 2015) – and three of the “Prêmio Jabuti” (Brazil) in the years 2015 and 2016 in the category “Infantil Digital” – “Não, sim, talvez” (MATSUSHITA, 2014), “Flicts” (ZIRALDO, 2014) and “A trilha” (ASSE, 2014) –, that work in different devices in the mobile operating systems iOS and/or Android. This is a qualitative-interpretative research (MINAYO, 2001; MOITA LOPES, 1996), based on an exploratory approach (GIL, 2016), whose theoretical-methodological framework is anchored in the dialogical conception of language, elaborated by the Circle of Bakhtin (VOLÓCHINOV, 2017), in multiliteracies studies (NEW LONDON GROUP, 2000; COPE; KALANTZIS, 2000, 2009a, 2009b), reading and the formation of the reader (JOUVE, 2002; RIBEIRO, 2011a; COSCARELLI, 2016; COSSON, 2016), digital picturebook (KIRCHOF, 2009, 2014, 2016; STICHNOTHE, 2014; YOKOTA; TEALE, 2014; GARCÍA-RODRÍGUEZ; GÓMEZ-DÍAS, 2016; SERAFINI; KACHORSKY; AGUILERA, 2016; MENEGAZZI, 2018), among others. To carry out the study it is proposed an evaluation matrix, consisting of indicators for analysis of the corpus, considering the multiliteracies practices. The elements for composition of the matrix cover the categorization of the book apps, the aspects that mobilize reading and multimodal literary literacy, textual multimodality and interaction resources, and structural aspects. The analysis of the six selected books showed that reading in interactive digital environments is characterized by being more complex in function of involving different types of knowledge previously obtained, such as the elements that make up the operational systems and management of mobile devices. In this book apps, interactivity requires the reader's performance and agentivity to make connections between distinct objects, allowing for deliberate movement through content in a non-linear way. It was found that the design of the picturebooks based on the effects produced by the verbovisual registers in double page was transposed directly to the digital screen, usually appearing on only one page/screen, and the animation features the task of simulating the effects characteristic of the traditional page turn, through agency. Even so, it has been confirmed that the presence of multiple multimodal combinations in children's book apps, coupled with reader agentivity and the affordances of digital technologies, requires more interactivity on the part of the reader and triggers differentiated modes of reading that contribute to the expansion of the possibilities of production of meaning.